Hubungan Perilaku Merokok Dengan Kejadian Hipertensi Pada Anggota Polri di Polda Bali - Eka Prasetya, I Putu Herry; Muliawati, Ni Kadek; Thrisna Dewi, Ni Luh Putu; Gede Putra, I Gusti Ngurah (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Hypertension is one of the major risk factors for cardiovascular disease and remains a global health problem. Smoking is known to increase blood pressure through mechanisms of vasoconstriction and endothelial damage. Police officers, who are exposed to high physical and mental work stress, are at risk of developing hypertension, particularly if they engage in smoking behavior. This study aimed to analyze the relationship between smoking behavior and the incidence of hypertension among police officers at the Bali Regional Police (Polda Bali). A quantitative cross-sectional design was employed, involving 90 police officers selected through stratified random sampling. Data on smoking behavior were collected using a questionnaire based on Smet’s theory (1994), while blood pressure was measured using a digital sphygmomanometer. Data were analyzed descriptively and inferentially using the Chi-Square test. The results showed that 51.1% of respondents had hypertension. Based on smoking categories, 32.2% were moderate smokers, 25.6% light smokers, 12.2% heavy smokers, and 30.0% non-smokers. The Chi-Square test indicated a significant association between smoking behavior and hypertension (p<0.001), with 91.0% of heavy smokers experiencing hypertension compared to only 11.1% among non-smokers. In conclusion, smoking behavior is significantly associated with the incidence of hypertension among police officers in Polda Bali. Health education and smoking cessation programs are essential interventions to reduce the risk of hypertension in this group.